The Impact of Social Media, Herding Bias, Gambler’s Fallacy, and Framing Effect on Investment Decisions among Gen Z Investors in Pontianak City - Felia Anadita Fitri; Dedi Hariyanto (Proceedings Series on Social Sciences & Humanities, 2024)
The role of social media can influence an individual's decision-making behavior, particularly when information presentation is accompanied by bias or financial behavior, which can impact investors' psychology in determining their investment choices. The research employs an associative research method, aiming to explore the relationship between the role of social media, herding bias, gambler's fallacy, and framing effect in the investment decision-making process among Generation Z, who have grown alongside technological advancements. The sampling technique involves purposive sampling with predefined criteria, and a total of 200 respondents participated in the survey conducted through Google Forms. Data verification was carried out using SPSS 26. The findings and conclusions indicate that while social media does influence investment decisions, the impact is not statistically significant. In contrast, herding bias and gambler's fallacy do not have a significant influence on investment decision-making.